Listening Difficulties In Children - Nurul Fadilah Tambunan; Nadhifa Shofi Andara (JELT : Journal of English Education, Teaching and Literature, 2024)
That belief most likely developed as a result of a dearth of solid studies that distinguished between speech comprehension issues brought on by weaknesses in language or cognition and those coming from abnormalities in auditory processing. This article states that the term ‘‘listening difficulty‘‘is a catch-all for reported impairments in sound detection or speech understanding, which may be caused by auditory processing problems. Other possible causes include difficulties in language, cognition, and hearing. In order to ascertain the extent to which each possible cause of a child's hearing impairments contributes to their real challenges in life, a summary of the study that has to be conducted is given in the article's conclusion. This work presents a novel conceptual framework for quantifying the impact of various types of auditory processing disorders (APDs) on hearing impairments in children.